Ocean surface energy balance allows a constraint on the sensitivity of precipitation to global warming - Wei Wang (Nature Portfolio, 2021)
There is some disagreement between climate models about how much precipitation changes under global warming. Here, the authors use the ocean surface energy balance to constrain the sensitivity of precipitation to historical warming and find that it is increasing by 0.68 ± 0.51% per degree warming.